Narcissism, envy and life satisfaction of college facebook users. - Iquina, Briar Rose
This study aimed to examine narcissism, envy and life satisfaction of college Facebook users. The study also explored the relationship among the following variables: narcissism and envy, narcissism and life satisfaction, and envy and life satisfaction. The study examined whether a user?s level of narcissism can be detected by other people through viewing their personal web pages. A survey was undertaken to answer the research objectives. There were two groups of participants in the study: (1) the 140 owner participants who answered the questionnaires and provided their Facebook profiles and (2) five raters who assessed the profiles of the owner participants. The results revealed that only the number of friends is correlated with narcissism. Frequencies of status and photo upload are not correlated with narcissism. Narcissism and envy are not correlated with each other. There is no relationship between narcissism and life satisfaction. Envy and Life Satisfaction is negatively correlated with each other. Strangers cannot predict the level of narcissism of Facebook users through just browsing at their profiles.